The The Effect Of Content Marketing on Instagram @Warkopshearlock On Purchase Interest Consumer in Perspective Islamic Economics - Sardia; Semaun, Syahriyah; Bahri, Andi; Muhammadun, Muzdalifah; Damirah, Damirah (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2024)
The growth of content marketing is encouraging social media users to engage in online marketing, which focuses on producing and sharing useful, timely, and consistent material to attract and retain a defined audience. This ultimately motivates clients to make profitable decisions. Through Instagram, @warkopshearlock uses content marketing to promote its products. The posts shared by Instagram @warkopshearlock through Instagram features aim to draw attention to the product and encourage customers to purchase it. This research aims to determine the extent to which consumer purchase interest is influenced by content marketing on Instagram @warkopshearlock. The technique used is a quantitative approach. Researchers used questionnaires to collect data. The population in this study consists of Warkop Shearlock's customers. Researchers employed purposive sampling techniques. To assess the extent of the influence between variables X and Y, researchers processed the questionnaire test data using Smart PLS 4. Based on the hypothesis test for the Content Marketing Variable (X), the t-statistic value is 13.321 > 1.96 or the p-value is 0.000 < 0.05, so H1 is accepted, meaning that Content Marketing on Instagram @warkopshearlock affects Consumer Purchase Interest. This indicates that H1 is accepted and Ho is rejected.